As‐indicated versus routine vision screening of preterm children: a 17‐year retrospective regional study. Issue 2 (17th August 2019) - Welinder, Lotte; Bender, Lars; Eriksen, Helle Højmark; Nissen, Kamilla Rothe; Ebbesen, Finn
Abstract: Purpose: To investigate outcomes of routine vision screening compared to as‐indicated ophthalmological investigation of all children born preterm in a Danish region from 1997 to 2014. Methods: All children born preterm (gestation age < 32 weeks or birthweight < 1500 g) screened for retinopathy of prematurity (ROP) were divided into two groups. From 1997 to 2009, only children treated for ROP or referred for visual problems received ophthalmological investigation (as‐indicated group). From 2010 to 2014, all ROP‐screened infants were offered ophthalmological investigation at 6 months and 3 years of age (screening group). Results: A total of 560 children were included in the as‐indicated period, 41 and 87 were referred for ophthalmological investigation at 6 months and 3 years, respectively. In the screening period, 295 children were included, 251 and 150 of whom underwent vision evaluation at 6 months and 3 years, respectively. Mean visual acuity was 4.1 cycles per degree with Teller acuity cards at 6 months and 0.78 decimal at 3 years. At 3 years, 2.7%( n = 11) in the as‐indicated versus 3.5%( n = 10) screening group had visual acuity < 6/18 (p = 0.24). Cerebral palsy ( n = 28) and epilepsy ( n = 5) were significantly related to vision impairment (p = 0.001/0.006), while treated ROP was not ( n = 13). Refractive error was common at 3 years (61%), especially astigmatism (50%). Gestational age, birthweight and ROP were not associated with vision impairment or refractive error. Conclusion: Screening preterm children at 6 months and 3 years did not reveal more visually impaired children compared to examination when indicated.